PENGARUH QUALITY OF WORK LIFE TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Kasus Balai Pelayanan Teknis Industri Kulit Di Magetan) - Dr. Sonang Sitohang, MM (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
The objective of this research is to analize the impact of the Quality of Work Life (QWL) to the Employee Productivity of Technical Leather Industry Unit Service in Magetan simustaneously either partial and also recognize that the Extencive Training is the dominant variable. The research population are 41 people, all the employees of Technical Leather Industry Unit Service in Magetan, and used multiple regression method to test hypotheses. Base on the research, the QWL that consist of; job security, selective hiring, self management team, equitable compensation, extensive training, reduced differences in status, and sharing information simultaneously have impact to the employee productivity (F) value 11,5206. So, With partial QWL to the employee productivity with (t) value; job security 4,4070, selective hiring 3,1928, self management team 6,4529, equitable compensation 4,1858, extensive training 7,1086, reduced differences in status 5,0497, and sharing information 4,0763, and the extencive training is the dominant variable to the employee productivity